Integration of the Securities Market Infrastructure in the European Union : Policy and Regulatory Issues - Kazarian, Elias (IMF Working Papers; Working Paper, 2006)
This paper examines the impact of ongoing cross-border integration of securities market infrastructure in the European Union. In particular, it analyzes the regulatory framework that has evolved to deal with the risks associated with cross-border clearing and settlement and concludes that, due to institutionalized deficiencies, the current cross-border regulatory framework may not be adequate or effective in addressing and preventing a real cross-border crisis. The paper proposes a two-tier regulatory framework for securities infrastructure in Europe entailing the creation of a centralized "federal" European regulatory framework for regional systems, in addition to the current national regulatory framework for domestic systems.